2014
DOI: 10.1002/imhj.21478
|View full text |Cite
|
Sign up to set email alerts
|

A Long-Term Follow-Up of a Randomized Controlled Trial of Mother-Infant Psychoanalytic Treatment: Outcomes on the Children

Abstract: A randomized controlled trial (RCT) compared two groups of mother-infant dyads in a Stockholm sample. One had received mother-infant psychoanalytic treatment (MIP group) and the other Child Health Center care (CHCC group). Effects were found on mother-reported depression and expert-rated mother-infant relationship qualities and maternal sensitivity. When the children were 4½ years old, they were followed up with assessments of attachment representations, socioemotional development, and global functioning. They… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 97 publications
(106 reference statements)
0
13
0
17
Order By: Relevance
“…Between‐group differences were found on the children in favor of MIP on global functioning and psychological well‐being (M.W. Salomonsson et al., ). The present article reports on outcomes on the mothers and the mother–child interactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Between‐group differences were found on the children in favor of MIP on global functioning and psychological well‐being (M.W. Salomonsson et al., ). The present article reports on outcomes on the mothers and the mother–child interactions.…”
Section: Discussionmentioning
confidence: 99%
“…After careful observations of each child, the interviewer formed categories through a process of induction (Philips, Werbart, Wennberg, & Schubert, ; Wachholz & Stuhr, ) into two major categories: “OK” and “Troubled.” Cognitive functioning was rated with the Wechsler preschool and primary scale of intelligence‐III (WPPSI‐III; Wechsler, , ). For a detailed account, refer to the report on the children (M.W.Salomonsson et al., ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data collected 6 months later indicated that the mothers in the MIP group had better results on self‐reported maternal depression, observer‐rated mother–infant relationships, and maternal sensitivity, and on a marginally significant level, self‐reported maternal stress. A follow‐up study of the long‐term outcomes for mothers and infants was initiated approximatively 3½ years after treatment termination when the children were 4½ years old (Winberg Salomonsson, Sorjonen, & Salomonsson, , ).…”
Section: The Infant Studymentioning
confidence: 99%
“…Quantitative outcome studies of parent–infant psychotherapy have been numerous (Cohen, Lojkasek, Muir, Muir, & Parker, ; Cooper, Murray, Wilson, & Romaniuk, ; Hayes, Matthews, Copley, & Welsh, ; Letourneau et al., ; Murray, Cooper, Wilson, & Romaniuk, ; Ravn et al., ; Robert‐Tissot et al., ; Santelices et al., ; Winberg Salomonsson et al., , ). Another way of investigating the development of the relationship between mother and child is the single case study of therapy cases (Baradon, Biseo, Broughton, James, & Joyce, ; Belt et al., ; Downing, Burgin, Reck, & Ziegenhain, ; Kächele, Schachter, & Thomä, ; Keren, ; Tuters, Doulis, & Yabsley, ; Willemsen, Della Rosa, & Kegerreis, ).…”
Section: The Infant Studymentioning
confidence: 99%